Public Policy for Academic Quality
X, 271 p.
Keywords: This volume summarizes a significant body of research systematically analyzing innovative external quality assurance policies in higher education around the world. It will be essential reading for policy makers, administrators and researchers alike. Over the last decade the structure of higher education in most countries has undergone significant change. This change, brought about by social demands for expanded access, technological developments, and market forces, has seen the traditional concerns with access and cost supplemented by a fresh concern with academic quality. As a result new public policies on academic quality assurance have rapidly emerged and migrated around the globe. However, the public debate about new academic quality assurance policies, both within and across countries, has not always been informed by reliable analyses of the strengths and weaknesses of these innovative instruments. It is this gap that the current edited volume seeks to fill. It is based on the work of the Public Policy for Academic Quality research program (PPAQ), which was designed to provide systematic analyses of innovative external quality assurance policies around the world. This volume, informed by key international scholars, presents the fourteen analyses conducted as part of the PPAQ research program. Each analysis examines the policy goals, implementation problems, and impacts of these newly developed national quality assurance instruments. The book concludes with an assessment of the lessons learned from these collected policy analyses and outlines the framework conditions that appear essential for assuring academic standards in the university sector.